2015
DOI: 10.1016/j.jab.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding: Antioxidative properties of breast milk

Abstract: Birth is an event that exposes the newborn baby to a high concentration of free radicals (reactive oxygen species (ROS) / reactive nitrogen species (RNS)), which can contribute to several diseases. The balanced equilibrium between ROS / RNS and the antioxidant system of the newborn is a key factor in preventing a plethora of diseases. The antioxidant system involves endogenous and exogenous molecules, from vitamins (A, E, C), to enzymes (glutathione peroxidase, superoxide dismutase), metals (copper (Cu), zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 81 publications
(105 reference statements)
0
20
0
2
Order By: Relevance
“…Studies on three continents found that when children were not breastfed in the second year, their risk of dying from infectious disease was almost twice that of breastfed infants 14 . Thus, breast milk contributes to health as a source of endogenous and exogenous molecules from vitamins (A, E, and C), minerals (Cu, Zn, and Se), endogenous enzymes (SOD and CAT), iodine 32 , bioactive factors such as immunoglobulins (IgA/sIgA, IgG, and IgM), cytokines (IL-6, IL-7, and IFN- γ), growth factors (EGF and BNDF), hormones and metabolic factors (calcitonin, lactoferrin, adiponectin, and leptin). Together, these factors recruit immunological cells, protect against infections, enhance intestinal and neuronal development and stimulate the antiviral and anti-inflammatory systems 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on three continents found that when children were not breastfed in the second year, their risk of dying from infectious disease was almost twice that of breastfed infants 14 . Thus, breast milk contributes to health as a source of endogenous and exogenous molecules from vitamins (A, E, and C), minerals (Cu, Zn, and Se), endogenous enzymes (SOD and CAT), iodine 32 , bioactive factors such as immunoglobulins (IgA/sIgA, IgG, and IgM), cytokines (IL-6, IL-7, and IFN- γ), growth factors (EGF and BNDF), hormones and metabolic factors (calcitonin, lactoferrin, adiponectin, and leptin). Together, these factors recruit immunological cells, protect against infections, enhance intestinal and neuronal development and stimulate the antiviral and anti-inflammatory systems 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, milk has antioxidant properties. However, the composition of human milk is affected also by such external factors as mother’s diet, lifestyle, and potential environmental pollutants (Andreas et al 2015 ; Emmett and Rogers 1997 ; Gomez-Gallego et al 2016 ; Mandal et al 2014 ; Matos et al 2015 ).
Fig.
…”
Section: Human Milk Compositionmentioning
confidence: 99%
“…O ovo representa uma importante fonte nutricional, por apresentar grande quantidade de aminoácidos essenciais, vitaminas e minerais, além de possuir fácil digestão e absorção. Sua importância destaca-se ainda pela ampla disponibilidade para todas as classes sociais no Brasil, uma vez que é um alimento de fácil aquisição por sua comercialização ser de baixo custo, contribuindo assim, para melhorar os aspectos nutricionais da dieta alimentar das famílias de baixa renda (FIUZA, 2014;RIBEIRO et al, 2015).…”
Section: Introductionunclassified
“…Dessa forma recomenda-se a suplementação para lactantes, visando melhorar o teor de vitaminas no leite(MORROW, 2019).O leite materno contém as vitaminas A, C, D, E, K e complexo B; responsáveis por funções como, crescimento, formação óssea, formação do sistema imunológico, desenvolvimento das funções neurológicas, entre outras. O leite humano é considerado fonte de vitaminas e suas concentrações diminuem ao longo da lactação, enquanto suas propriedades antioxidantes totais aumentam(MATOS et al, 2015).Em geral,Erick (2018) relata que a composição do leite materno é insuficiente, em relação a certos nutrientes, em países em desenvolvimento, como por exemplo, as vitaminas A, D, K, B12, B1. Ao apresentar deficiências nutricionais, em países com poucos recursos, a mesma deficiência será levada adiante via lactação.…”
unclassified